Getúlio Vargas encadernado: a construção narrativo-argumentativa da imagem do estadista em Getúlio Vargas, meu Pai - Raquel Lima de Abreu (2016)
The objective of this research was to analyze the biography Getúlio Vargas, my Father, written by the biographed mans daughter Alzira Vargas, mainly seeking to verify which ethé have been outlined for Vargas, in order to comprehend, through them, the image of the statesman she wished to crystallize for posterity. As to the theoretical framework we have emphasized the Semiolinguistics Theory of Charaudeau; the Discourse Organization modes, also by this author; and studies on the ethos. In relation to the latter category we highlight that, at first, we revisited the concept of ethos in the light of the old sophistic rhetoric, and of the classicals, which include: Plato, Isocrates, Aristotle, Cicero and Quintilian. Thereupon we sought for contemporary contributions to this category in the works of Perelman, Charaudeau, Amossy, Maingueneau and Hannah Arendt. We would like to point out that, being a biography that is also permeated with historical dominion, it was necessary to analyze Getúlio Vargas, my Father in an interdiscursive way, using elements from that dominion. Based on this analysis, we can say that our expectations for this biography have been frustrated, since we believed that a biography written by the statesmans daughter would go far beyond historical facts, and adopt a more intimate and personal perspective, which, by the way, the author promised both in the title of her work and the introduction. However, unlike that, Alzira Vargas hardly speaks of Getúlio, her father, but instead she speaks of Getúlio, her gaffer, her boss and a statesman. We have also observed that the ethé designed for the protagonist attribute countless virtues to him, and records scarcity of vicious acts, which in their turn, were always justified by the author. Therefore, the presented image of Getúlio Vargas in this biography was highly positive, which is questionable.